Use of auxin to delay ripening: sensory and biochemical evaluation of Cabernet Sauvignon and Shiraz. (19th August 2021) - Böttcher, C.; Johnson, T.E.; Burbidge, C.A.; Nicholson, E.L.; Boss, P.K.; Maffei, S.M.; Bastian, S.E.P.; Davies, C.
Abstract: Background and Aims: Climate change is prompting earlier grape ripening and harvest compression causing quality and logistical problems for growers and winemakers. Application of 1‐naphthalene acetic acid (NAA) offers a management tool to delay ripening and expand the harvest window. This study extends previous findings about the effect of NAA on Shiraz fruit and wine composition and provides the first analysis of NAA‐induced ripening delay of Cabernet Sauvignon. Methods and Results: Pre‐veraison NAA treatment of Shiraz and Cabernet Sauvignon grapes delayed harvest maturity by 3–4 weeks. Modification of nutrient accumulation was minor, and wines made from NAA and Control fruit displayed no significant variation in basic chemical properties. The concentration of methoxypyrazine in NAA‐treated Cabernet Sauvignon grapes was unaffected, whereas NAA‐treated Shiraz fruit and wine contained an elevated concentration of rotundone. The overall difference in wine volatile profiles between NAA and Control was small for both cultivars, reflected by Rate‐All‐That‐Apply assessments that found no (Cabernet Sauvignon) or few (Shiraz) sensory attributes distinguishing the wines. Conclusions: Application of NAA delays winegrape ripening with small, cultivar‐dependent effects on grape and wine composition, that are unlikely to negatively affect wine sensory perception. Significance of the Study: This work further establishes NAA as a ripening‐delay agent that could be used commercially to delay grape maturation and decompress harvest while preserving berry integrity and wine typicity.